Effects of Spacing between Items and View Direction on Errors in the Perceived Height of a Rotated 3-D Figure. Issue 1 (August 2014) - Chen, Chen-Fu; Lin, Chin-Chiuan; Huang, Kuo-Chen
This study investigated the errors in the perceived height of virtual cones presented on the screen. 80 students (50 women, 30 men; M age = 18.8yr., SD = 1.2 using a duodecimal system) participated in the study. They judged the height of virtual cones in several conditions: (a) different spaces between the items in the array (2, 4, and 6 cm); (b) different viewing directions – bottom-up or top-down; (c) cones presented in different forward-rotated angles (15, 30, and 45°). Results indicate that fewer errors in the perceived heights of virtual cones were made when: the space between items was 2 cm, judgment was made in a bottom-up view and at a 15° angle. These results may have implications for graphics-based interface design such as interior design, driver navigation systems, geological models, and flight-simulation systems.